The impact of risk preference on farmers’ e-commerce operations: evidence from rural China - Qiu, Hailan; Wu, Xiangqi; Peng, Ruohan; Wang, Jiawei; Sheng, Biao (Frontiers in Sustainable Food Systems, 2025)
IntroductionFarmers’ own risk attitudes are important for e-commerce operations and digital transformation of rural economy.MethodsBased on the 3,670 farmers data of China Rural Revitalization Survey, using binary logit model and mediation effect model, this paper discusses the impact of risk preference on farmers’ e-commerce operations and its mechanism, and examines the heterogeneous impact of road condition, network outlet construction and regional distribution. Building on this analysis, it further discusses differences in the impact across operation scales, operation models, technology utilizations and product types.Results and discussionThe results indicate that risk preference significantly increases the likelihood of farmers’ participation in e-commerce operations, and this finding remains robust after both robustness and endogeneity tests. Mechanism analysis reveals that risk preference promotes e-commerce operations through both formal and informal lending channels. Heterogeneity analysis shows that the effect is stronger for farmers with favorable road condition, well-developed network outlet, and in the central and western regions. Further analysis demonstrates that the promoting effect of risk preference is particularly pronounced for large-scale e-commerce, social e-commerce, and live-streaming e-commerce, and is especially strong in transactions involving primary processed products. The findings suggest the need to establish a hierarchical support mechanism that accommodates differences in farmers’ risk preference, while simultaneously advancing innovations in rural financial services and strengthening the development of e-commerce infrastructure. In addition, differentiated guidance should be provided to foster innovative e-commerce models and to optimize the overall e-commerce ecosystem, thereby unlocking the full development potential of rural e-commerce and contributing to sustainable rural revitalization.